Eyeshadow as a Fashion Cosmetic in Review of Hadith: Celak Mata sebagai Fashion Kosmetik dalam Tinjauan Hadis (Takwil: Journal of Quran and Hadith Studies, 2023)
The use of eyeshadow using itsmid has become a habit carried out by the Prophet Muhammad and of course this is also a recommendation for his people. In a hadith narrated by Ibn Majah it is stated that kohl made from itsmid material can clear the eyes and lengthen the eyelashes. Today, eyeshadow is more widely used by women as a fashion in the world of cosmetics and beauty. The materials used have also undergone variations, no longer made from itsmid. This study examines the hadiths of wearing eyeshadow, and reviews the contextualization of this hadith using eyeshadow as a fashion. This type of research is literature with takhrij and ma'anil hadith approaches. The results of the study show that the hadiths about celak are listed in six source books, namely sunan Abu Dawud, sunan at-Tirmidhi, sunan Ibnu Majah, sunan ad-Darimi, sunan an-Nasa'i, and musnad Ahmad bin Hanbal. The best kolak is itsmid which comes from the country of Ashbahan in the form of very black, almost reddish stones. Itsmid celak functions as an eye medicine, which sharpens eyesight, grows eyelashes. However, based on the purpose and benefits of wearing kohl, using kohl other than itsmid is permissible, as well as for fashion purposes, as long as it's not excessive, which doesn't harm eye health.